PERBANDINGAN KADAR GULA DARAH SEWAKTU DAN ASAM URAT PADA PENDERITA STROKE ISKEMIK DENGAN STROKE HEMORAGIK DI RUMAH SAKIT UMUM HAJI MEDAN PROVINSI SUMATERA UTARA TAHUN 2018 – 2019 - ANDRE PRAMUDIA KRISNA; ISRA THRISTY (JURNAL ILMIAH MAKSITEK, 2021)
Stroke is a major cause of death and disability in many countries. Risk factors for stroke include hypertension,hyperlipidemia, hyperuricemia, DM. Data on risk factors for stroke nationally are not yet known with certainty so that furtherresearch needs to be done. This study aims to determine the comparison of blood sugar levels and uric acid in patients withischemic and hemorrhagic strokes at Haji General Hospital Medan City in 2018-2019. This type of research is analyticdescriptive. The approach used in this study is retrospective. Data were processed using SPSS Mann-Whitney test.There was no significant difference in blood sugar levels between ischemic stroke and hemorrhagic stroke (p = 0.233). Therewas a significant difference in uric acid between ischemic stroke and hemorrhagic stroke (p = 0.00). There was no significantdifference in blood sugar levels between ischemic stroke and hemorrhagic stroke. While there are significant differences inuric acid levels between ischemic stroke and hemorrhagic stroke.